2022
DOI: 10.3389/fpubh.2022.882686
|View full text |Cite
|
Sign up to set email alerts
|

Influence of circulating nesfatin-1, GSH and SOD on insulin secretion in the development of T2DM

Abstract: AimsTo evaluate the correlation of nesfatin-1, GSH and SOD levels with β-cell insulin secretion and their influence on insulin secretion in the development of type 2 diabetes mellitus (T2DM).Materials and methods75 patients with T2DM, 67 with prediabetes and 37 heathy participants were recruited in this study. Serum levels of nesfatin-1, GSH and SOD were quantified and statistically analyzed.ResultsThe levels of nesfatin-1, GSH and SOD in T2DM were significantly decreased (P < 0.001) compared to either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Regarding serum nesfatin-1 level, our study was in line with previous studies as those conducted by Li et al [ 22 ] and Kadim and Hassan [ 23 ], which showed significantly lower nesfatin-1 in the T2DM patients in comparison to the control group. Also, these results were in agreement with the studies done by Matta et al [ 24 ] and Huang et al [ 25 ] who found that nesfatin-1 is lower in both T2DM and prediabetic patients. According to a systematic review and meta-analysis conducted by Zhai et al [ 26 ] for the assessment of circulatory nesfatin-1 levels and T2DM, patients who were just diagnosed with the disease had higher levels of nesfatin-1, while those who were receiving antidiabetic treatment had lower levels.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding serum nesfatin-1 level, our study was in line with previous studies as those conducted by Li et al [ 22 ] and Kadim and Hassan [ 23 ], which showed significantly lower nesfatin-1 in the T2DM patients in comparison to the control group. Also, these results were in agreement with the studies done by Matta et al [ 24 ] and Huang et al [ 25 ] who found that nesfatin-1 is lower in both T2DM and prediabetic patients. According to a systematic review and meta-analysis conducted by Zhai et al [ 26 ] for the assessment of circulatory nesfatin-1 levels and T2DM, patients who were just diagnosed with the disease had higher levels of nesfatin-1, while those who were receiving antidiabetic treatment had lower levels.…”
Section: Discussionsupporting
confidence: 93%
“…Various enzymes prevent oxidative stress. As an illustration, SOD1 turns superoxide radicals into hydrogen peroxide, which GSH peroxidase then transforms into water (K. Huang et al, 2022). Therefore, we hypothesize that reducing ROS levels by increasing enzyme expression will induce oxidative stress resistance and improve the ischemic flap survival rate.…”
Section: Resultsmentioning
confidence: 99%
“…When MDA is released from the cells, it can alter the permeability of the membrane, resulting in structural and functional damage, and can react with proteins and nucleic acids to initiate cross-linking polymerization and disrupt regular metabolic reactions ( Tsikas, 2017 ). Oxidative stress damage and antioxidant capacity can be significantly improved by endogenous antioxidant enzymes SOD and non-enzymatic GSH ( Huang et al, 2022 ). Our results showed that supplementation of heat-treated or Lactobacillus rhamnosus can lower the levels of MDA in both the serum and brain tissues, increase those of SOD and GSH, and limit the degree of peroxidation.…”
Section: Discussionmentioning
confidence: 99%